Do international factors influence the passage of climate change legislation?. (2nd April 2016) - Fankhauser, Samuel; Gennaioli, Caterina; Collins, Murray
Abstract : The number of climate change laws in major economies has grown from less than 40 in 1997 to almost 500 at the end of 2013. The passage of these laws is influenced by both domestic and international factors. This article reviews the main international factors, drawing on a powerful new dataset of climate legislation in 66 national jurisdictions. We find that the propensity to legislate on climate change is heavily influenced by the passage of similar laws elsewhere, suggesting a strong and so far under-appreciated role for international policy diffusion. International treaties such as the Kyoto Protocol work in two ways. The impact of the Kyoto Protocol itself is limited to countries with formal obligations under the treaty. In addition, the prestige of hosting an international climate summit is associated with a subsequent boost in legislation. Legislators seem to respond to the expectations of climate leadership that these events bestow on their host. Policy relevance A global solution to climate change will ultimately have to be anchored in domestic legislation, which creates the legal basis for countries to take action. Countries are passing climate legislation in a growing number. This article asks to what extent they are motivated to do so by international factors, such as existing treaty obligations. We find that the Kyoto Protocol has been a less important factor in explaining climate legislation outside Annex I than the passage of similar laws elsewhere. This suggests that international policy diffusion plays an important and so far under-appreciated role in global climate policy, complementing formal treaty obligations.